2010
DOI: 10.1371/journal.pone.0011605
|View full text |Cite
|
Sign up to set email alerts
|

Two Origins for the Gene Encoding α-Isopropylmalate Synthase in Fungi

Abstract: BackgroundThe biosynthesis of leucine is a biochemical pathway common to prokaryotes, plants and fungi, but absent from humans and animals. The pathway is a proposed target for antimicrobial therapy.Methodology/Principal FindingsHere we identified the leuA gene encoding α-isopropylmalate synthase in the zygomycete fungus Phycomyces blakesleeanus using a genetic mapping approach with crosses between wild type and leucine auxotrophic strains. To confirm the function of the gene, Phycomyces leuA was used to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…same common ancestor (Larson & Idnurm, 2010). LeuC has a C-terminal extension absent in both Leu4p and Leu9p.…”
Section: Resultsmentioning
confidence: 99%
“…same common ancestor (Larson & Idnurm, 2010). LeuC has a C-terminal extension absent in both Leu4p and Leu9p.…”
Section: Resultsmentioning
confidence: 99%
“…Genes that have been sequenced and also mapped based on mutant phenotypes in Phycomyces are: carRA and carB that control biosynthesis of β-carotene [45], [46]; the sex mating type locus [39]; madA and madB that encode a blue light photoreceptor complex [35], [36]; leuA and purC that are linked auxotrophic markers [47]; pyrG [26], [48]; and recently carS for cleavage of β-carotene [49], [50]. Knowledge of other genes would help link the two maps more thoroughly.…”
Section: Discussionmentioning
confidence: 99%
“…For mapping mutations to parts of the chromosome, bulked segregant analysis and genome resequencing could be used, as has been successful for mapping in Neurospora crassa [61]. We have already applied these PCR-RFLPs for map-based identication of four genes, carS , leuA , madC and madI , and narrowing the DNA regions for others ([47], [49] and unpublished data). The identification of the furA , lysA and nicA genes adjacent to madD , madE and carC genes, respectively, should facilitate the identification of genes required for phototropism and biosynthesis of β-carotene.…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes the first enzyme dedicated to the biosynthesis of leucine. Previous research on the evolution of this gene in the fungal kingdom demonstrated two distinct groups, one found in the Dikarya species and the other in the basal non-Dikarya fungi (Larson and Idnurm, 2010). However, the function of the gene in the basidiomycetes had not been assessed by gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind targeting LEU1 was threefold. First, homologs were under investigation in a zygomycete and ascomycete in the laboratory for understanding LEU1 evolution in the fungal kingdom (Larson and Idnurm, 2010), and the Sporobolomyces sp. mutation would provide experimental evidence for the function of this form of the gene in leucine biosynthesis within the basidiomycetes.…”
Section: Biolistic Transformation Of Strain Iam 13481 and The Targetmentioning
confidence: 99%